Platelet count and mean volume in acute stroke: a systematic review and meta-analysis - Farzaneh Sadeghi; Sándor Kovács; Katalin Szilvia Zsóri; Zoltán Csiki; Zsuzsanna Bereczky; Amir Houshang Shemirani (Platelets, 2020)
Changes of mean platelet volume (MPV) and platelet count (PC) could be a marker or a predictor of acute stroke (AS). We conducted a systematic review and meta-analysis of the published literature on the reporting of MPV and PC in AS. Studies were included in accordance with Patient Population or Problem, Intervention, Comparison, Outcomes, and Setting framework. The PRISMA strategy was used to report findings. Risk of bias was assessed with the Newcastle-Ottawa Scale. We included 34 eligible articles retrieved from the literature. PC was significantly lower in AS patients [standardized mean difference (SMD) = − 0.30, (95% CI: − 0.49 to − 0.11), N = 2492, P = .002] compared with controls (N = 3615). The MPV was significantly higher [SMD = 0.52 (95% CI: 0.28–0.76), N = 2739, P < .001] compared with controls (N = 3810). Subgroup analyses showed significantly lower PC in both ischemic stroke (Difference SMD = −0.18, 95% CI: −0.35–0.01) and hemorrhagic stroke (−0.94, −1.62 to −0.25), but only samples by citrate anticoagulant showed significantly lower result for patients compared to controls (−0.36, −0.68 to −0.04). Ischemic stroke patients had higher MPV (0.57, 0.31–0.83), and samples by Ethylenediaminetetraacetic acid (EDTA) anticoagulant showed significantly higher result for patients compared to controls (0.86, 0.55–1.17). PC and MPV appeared to be significantly different between patients with AS and control populations. MPV was significantly higher in ischemic stroke and PC was significantly lower in both ischemic and hemorrhagic strokes. These characteristics might be related to AS and associated with it. It is advisable to pay attention to elapsed time between phlebotomy and hematology analysis, anticoagulant and hemocytometer types in AS. Systematic review registration This meta-analysis is registered on the International Prospective Register of Systematic Reviews (PROSPERO) under registration number CRD42017067864 (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=67864).